Clumped isotope effects of thermogenic methane formation: Insights from pyrolysis of hydrocarbons. (15th June 2021) - Dong, Guannan; Xie, Hao; Formolo, Michael; Lawson, Michael; Sessions, Alex; Eiler, John
Abstract: Methane clumped isotope analysis is a tool used to constrain the formation or equilibration temperatures of methane, or to differentiate methane of thermogenic, microbial or 'abiotic' origins. Geothermometry applications are based on the temperature dependence of relative abundances of multiply-substituted isotopologues in thermodynamic equilibrium, whereas assignments of biogenicity or 'abiogenicity' rely on kinetic isotope effects associated with synthesis, which disturb clumped isotope abundances away from expected equilibrium proportions. However, kinetic processes in thermogenesis or during post-generation storage of thermogenic gas may cause isotopic disequilibrium, confounding thermometry applications or leading to 'false positive' identifications of microbial or abiogenic gases. Non-equilibrated clumped isotope compositions have been observed in thermogenic gases including unconventional oil-associated gases and from coal pyrolysis experiments. The isotopic disequilibria might be caused by kinetic isotope effects expressed during gas migration (including extraction), or by irreversible chemical processes, such as breaking carbon–carbon bonds in an alkyl precursor. In this study, we performed controlled pyrolysis experiments at 400 °C on n-octadecane (C18 H38 ). We characterized the gas chemistry, and compound-specific carbon and hydrogen isotope and methane clumped isotope compositions of the gas products. We found that Δ 13 CH3 D values (anomalies relative to a stochastic distribution of isotopes) appear to be relatively close to equilibrium at the experimental temperature, whereas Δ 12 CH2 D2 values are 30–40‰ lower than expected for equilibrium. The large deficit in Δ 12 CH2 D2 can be explained by assembling hydrogen atoms affected by two distinct kinetic isotope effects into a methane molecule, previously referred to as a 'combinatorial effect'. We present a kinetic model that describes the full isotopic systematics, including anomalous Δ 12 CH2 D2 deficits, of pyrolysis product methane. Finally, we propose a model for the isotope signatures of natural thermogenic methane where the non-equilibrium Δ 12 CH2 D2 composition is a signature of the onset of catagenetic methane production. Our model also describes ways in which this signature disappears as further maturation drives Δ 12 CH2 D2 to equilibrium through hydrogen exchange. Our findings demonstrate that anomalous depletion in Δ 12 CH2 D2 is not a unique signature for microbial or putative abiotic methane, and specifically, it can be generated during pyrolytic chemistry.